2019
DOI: 10.1126/sciadv.aaw2778
|View full text |Cite
|
Sign up to set email alerts
|

Multiplexed analysis of the secretin-like GPCR-RAMP interactome

Abstract: Receptor activity–modifying proteins (RAMPs) have been shown to modulate the functions of several G protein–coupled receptors (GPCRs), but potential direct interactions among the three known RAMPs and hundreds of GPCRs have never been investigated. Focusing mainly on the secretin-like family of GPCRs, we engineered epitope-tagged GPCRs and RAMPs, and developed a multiplexed suspension bead array (SBA) immunoassay to detect GPCR-RAMP complexes from detergent-solubilized lysates. Using 64 antibodies raised again… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
71
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 65 publications
(73 citation statements)
references
References 43 publications
2
71
0
Order By: Relevance
“…3 B and C ). Since GPR182 has recently been described to be able to interact with receptor activity–modifying proteins (RAMPs) ( 22 ), we tested whether coexpression of RAMP-1, -2 or, -3 with GPR182 resulted in chemokine-induced G protein–mediated responses. However, none of the RAMPs promoted downstream signaling of GPR182 ( Fig.…”
Section: Resultsmentioning
confidence: 99%
“…3 B and C ). Since GPR182 has recently been described to be able to interact with receptor activity–modifying proteins (RAMPs) ( 22 ), we tested whether coexpression of RAMP-1, -2 or, -3 with GPR182 resulted in chemokine-induced G protein–mediated responses. However, none of the RAMPs promoted downstream signaling of GPR182 ( Fig.…”
Section: Resultsmentioning
confidence: 99%
“…Christopoulos et al (40) showed an interaction of RAMP2, but not RAMP1/3, with PTH1R using an assay based on trafficking to the cell surface in HEK293 cells. More recently, using a bead-based immunoassay with DDM-solubilized HEK293 cells expressing epitope-tagged receptors, Lorenzen et al (17) reported interaction of all three RAMPs with PTH1R. Interestingly, they also detected interactions of all three RAMPs with CLR in DDM.…”
Section: Discussionmentioning
confidence: 99%
“…Importantly, here we not only demonstrated GPCR•RAMP complex formation but also functionality by coupling to peptide ligands and mG proteins. Given the recent reports of RAMP interactions with numerous other GPCRs (17,18), most of which have not been further validated by other methods or tested for functional consequences, the hrCNE assay may be a useful method with which to examine some of these putative RAMP•GPCR complexes.…”
Section: Discussionmentioning
confidence: 99%
“…The NEBuilder HiFi DNA Assembly Tool was used to assemble the BRET 2 acceptor constructs CysLTR2–GFP10. These were assembled from three parts: pcDNA3.1(+) backbone from construct HA-CLIP-CLR ( 24 ), CysLTR2, and full-length C-terminal 1D4 epitope tag from FLAG-CysLTR2-1D4 mentioned above, and GFP10 from YB124_CXCR4–GFP10 ( 15 ). The primers ( Table S2 B ) were designed using the NEBuilder Assembly Tool on the NEB website with a specific sequence to prime to the gene of interest for template priming (3’ end), as well as an overlap sequence to aid in assembly (5’ end).…”
Section: Methodsmentioning
confidence: 99%